70.4k views
2 votes
3=7(4-2u)-6u can you help

User Ekeyme Mo
by
5.0k points

2 Answers

5 votes

u=5/4

Step-by-step explanation:

distribute and simplify right side of equation

3= 28−14u −6u

3=28−20u

subtract 28 from both sides

3−28=−20u

−25=−20u

divide both sides by

−20/ −25 = u ⇒ u =54

User Tommy Siu
by
5.8k points
7 votes

Answer:

5/4

Step-by-step explanation:

, open the bracket

3=28-14u-6u

Collect like terms

3-28=-14u-6u

-25 =-20u

Divide both side by -20

u=-25/-20. Minus sign will cancel each other and reduce to the lowest term

u=5/4

User James Tauber
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.